Independent effects of rapid eye movement sleep deprivation and exposure to environmental heat stress on aerobic performance and thermoregulatory responses in exercising rats - Shang, Felipe Lioe Teh (Temperature (Austin), 2020)
Evidence indicates that aerobic performance is degraded either by environmental heat stress or sleep deprivation. However, whether these conditions interact to produce more significant performance impairment deserves further investigation. Therefore, this study investigated the effects of experimental sleep deprivation (24 h or 96 h) on aerobic performance and thermoregulatory responses in rats exercised on a treadmill at different environmental conditions. Adult male Wistar rats were subjected to rapid eye movement sleep deprivation (RSD) using the modified multiple platform method and were then subjected to an incremental-speed exercise until they were fatigued. Treadmill running was performed in a temperate (24°C) or warm (31°C) environment, and the colonic temperature (an index of core body temperature; T(CORE)) and the tail-skin temperature (T(SKIN); an index of cutaneous heat loss) were recorded. 24-h and 96-h RSD produced small magnitude reductions in aerobic performance (Cohen’s d = 0.47–0.58) and minor changes in thermoregulation. Relative to control rats, sleep-deprived rats showed a higher T(CORE) at the exercise initiation and a higher threshold for activating cutaneous heat loss, but unchanged T(CORE) and T(SKIN) at fatigue. Exercise at 31°C induced large reductions in performance (d = 0.82–1.29) and marked changes in thermoregulation, as evidenced by higher T(CORE) and T(SKIN) at fatigue, compared to exercise at 24°C. Interestingly, none of the effects induced by RSD were exacerbated by environmental heat stress and vice-versa, indicating that both conditions did not interact. We conclude that RSD and heat stress modulate aerobic performance and thermoregulatory responses by acting independently.